ANALISIS IMPLEMENTASI WISATA KONVENSI (MICE) DI KUTA PARADISO HOTEL - Ni Luh Made Wijayati; I Made Widiantara; Ni Nyoman Supiatni; I Made Yudha Dibrata (Forum Manajemen STIMI Handayani Denpasar, 2022)
Tourism is one of the important economic sectors in Indonesia, because industry contributes to the country's foreign exchange. Convention tourism (MICE) is one of the tourism sectors that is being held by the Indonesian government, because convention tourists are seven (7) times more consumptive than leisure tourists. This study aims to determine the implementation of a tourist convention (MICE) at Kuta Paradiso Hotel. This research was conducted with a sample of 25 people. The analysis technique used is the SWOT analysis (Strength, Weakness, Opportunity, Threat). The results of this study indicate that in the Summary Internal Factor Analysis (IFAS) the score on strength is 2.10 and weakness is 1.09, so the value that can be used is a strength value of 2.10. In the Summary of External Factor Analysis (EFAS) the score on the opportunity is 2.03 and the challenge is 1.08, so the value that can be used is the probability value of 2.03. In the diagram, cartesius shows the position of the implementation of convention tourism (MICE) located in quadrant I is an aggressive strategy while this strategy shows a very favorable place. The implementation of convention tourism (MICE) at Kuta Paradiso Hotel has strengths and opportunities that are united and mutually supportive by using power factors to take advantage of existing opportunities.